2022
DOI: 10.1371/journal.pone.0262671
|View full text |Cite
|
Sign up to set email alerts
|

Time point- and plant part-specific changes in phloem exudate metabolites of leaves and ears of wheat in response to drought and effects on aphids

Abstract: Alterations in the frequency and intensity of drought events are expected due to climate change and might have consequences for plant metabolism and the development of plant antagonists. In this study, the responses of spring wheat (Triticum aestivum) and one of its major pests, the aphid Sitobion avenae, to different drought regimes were investigated, considering different time points and plant parts. Plants were kept well-watered or subjected to either continuous or pulsed drought. Phloem exudates were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…These serve as a primary nitrogen source for the aphids. Phloem sap varies in composition throughout the developmental stage of the plant, diurnal cycle, season, as well as abiotic factors such as temperature and water availability (Karley et al 2002;Stallmann et al 2022). The composition and concentration of such amino acids in the phloem is therefore an important indicator of aphid performance and hence populations (Douglas 1993;Karley et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These serve as a primary nitrogen source for the aphids. Phloem sap varies in composition throughout the developmental stage of the plant, diurnal cycle, season, as well as abiotic factors such as temperature and water availability (Karley et al 2002;Stallmann et al 2022). The composition and concentration of such amino acids in the phloem is therefore an important indicator of aphid performance and hence populations (Douglas 1993;Karley et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, the response of C suc to water deficit is somewhat variable. The water regime has been found to have little effect on sucrose concentration in leaf phloem exudates (Stallmann et al, 2022). Drought was found to increase total sucrose (as well as glucose and fructose) collected from leaf exudates, expressed in mg g −1 FW (Xie et al, 2022) while exudated sucrose was found to decrease (glucose and fructose being unchanged) in another study (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Per treatment group (i.e., plant species * water treatment * herbivory treatment), there were n = 8 biological replicates (pooled from three plants each, see below). Three days after the aphid infestation had started, phloem exudates of the leaves that had been bagged (either with or without aphids) were collected and analyzed according to Stallmann et al (2022). with some modifications.…”
Section: Metabolomics Of Phloem Exudatesmentioning
confidence: 99%
“…These nutrients will end up in the phloem sap and will thus be taken up by aphids, which might increase their performance Mezgebe and Azerefegne 2021;. Phloem exudation of amino acids like asparagine, leucine and in particular proline were affected by water stress Stallmann et al 2022). However, the extent and direction of these changes depend highly on the plant species and degree of stress the plants are subjected to.…”
Section: Introductionmentioning
confidence: 99%